Mentoring Elementary School Teachers' Competency Enhancement in Utilizing Digital Platforms and Interactive Content for Kurikulum Merdeka Implementation in Rural Areas - Mustamin, Kaso; Karmila, Mila; Sukmayadi, Dodi; Smas, Musa Hefer; Winarko, Triyugo (PT Inovasi Pratama Internasional, 2025)
This qualitative research investigates the effectiveness of a mentoring program designed to enhance elementary school teachers' competency in utilizing digital platforms and interactive content for implementing Kurikulum Merdeka in rural Indonesian areas. The study employed a comprehensive mentoring approach focusing on the Platform Merdeka Mengajar and interactive digital content creation to address the digital divide in rural education. Twenty elementary school teachers from remote areas participated in a 12-week structured mentoring program. Data collection utilized in-depth interviews, focus group discussions, participant observations, and document analysis. The findings reveal significant improvements in teachers' digital literacy, confidence in technology integration, and student engagement levels. Pre-mentoring assessment showed 65% of teachers had low digital literacy, which improved substantially post-intervention with 100% satisfaction rates among participants. Key challenges identified included limited internet connectivity, inadequate hardware, and insufficient technical training, which were addressed through innovative solutions including mobile hotspot sharing, device lending systems, and peer mentoring networks. The study demonstrates that systematic mentoring programs can effectively bridge the digital competency gap among rural teachers, enabling successful Kurikulum Merdeka implementation despite infrastructure limitations. This research contributes to understanding professional development strategies for educational transformation in underserved regions.